Effects of the therapeutic community modality program on inmates of Baguio City Jail, Philippines a discourse analysis - Fagaso, Connie A. and Yapo, Jerry R. (UP Los Baños Journal, 2014)
The study of investigated the effects of the Therapeutic Community Modality (TCM) program of Baguio City Jail (BCJ) using Critical Discourse Analsis as its approach. In the context of a jail institution in the Philippines. TCM aims to rehabilitate and reform inmates who are currently detained. Its goal is to reintegrate inmates back into society by attempting to effect some change in their behavior, emotions, intellect and vocation. This study probed the concept of power and authority present in the discourse of inmates and personnel of BCJ in the implementation of TCM from April to May of 2011. Informed by Critical discourse Analysis as its lens, the study applied Norman Fairclough's Three-Dimensional Model and that of Teun van Dijk. It sought to explain Baguio City Jail's TCM in terms of its methods and programs, and possible roles of inmates that emerged because of these. It also revealed new linguistics terms in the jail's discourse when this program was created. Finally, it analyzed changes in power relations between inmates and personnel. Research findings show that there is a positive impact of the TCM program on the behavioral, emotional, intellectual and vocational components of inmates. There is no discernible change, however, in power relations between inmates and personnel, and this may be attributed to the fact that jail is an institution governed by laws of the country.